Changes in Students' Educational Attitudes A Case Study of an Experimental Living-Learning Program - Morstain, Barry R.; Delaware Univ., Newark ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
With the recognition that different kinds of students desire different kinds of educational experiences, many colleges and universities have been moving to develop innovative programs in the undergraduate domain. One approach that has been gaining in popularity is based on the "living-learning" concept. This concept is an attempt to blend, rather than fragment, a student's in and out-of-class experiences. Such a program, called the Experimental Freshman Year Program (EPP), was implemented at the University of California, Davis. The program was housed in a coed dormitory and centered on the theme "Self in Society," Since the desired changes in students were behavioral and attitudinal, a means of evaluation called the Student Orientations Survey (SOS) was developed. The impact that the EPP had on freshman students is considered highly desirable according to the results of the SOS. Students seem to feel that they were more a part of the learning experience, had purpose in studying other than the reward of a grade, and had achieved a means of organizing thoughts and selves. (HS)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Freshmen; Educational Innovation; Experimental Programs; Higher Education; Relevance (Education); Student Centered Curriculum; Student Evaluation